ACCOUNTABILITY OF VILLAGE FUNDS MANAGEMENT - Savitri, Enni; Andreas, Andreas; Diyanto, Volta (Jurnal Aplikasi Manajemen, 2019)
This study analyzes the accountability and transparency of village funds management in Riau Province of Indonesia. In particular, it focuses the analysis on the implementation, reporting, planning, and accountability stages, to review the community participation in management ofvillage fund and the obstacles to its implementation. Research participants were chief of the villages, village secretaries and village treasurers of coastal villages in Riau Province.There were 31 respondents. Results showed that all stages of village management were in accordance with the existing provisions. Some obstacles were found in the program implementation. These include the lack of human resources, the community participating in all the procedures and stages of the village finances, the government conducting supervision, and giving guidance through counseling and training for village officials. In further research management of village financial using Siskeudes for financial reporting.